Linking root exudation to belowground economic traits for resource acquisition - Wen, Zhihui; White, Philip J.; Shen, Jianbo; Lambers, Hans (The New phytologist, 2022)
Summary The concept of a root economics space (RES) is increasingly adopted to explore root trait variation and belowground resource‐acquisition strategies. Much progress has been made on interactions of root morphology and mycorrhizal symbioses. However, root exudation, with a significant carbon (C) cost (c. 5–21% of total photosynthetically fixed C) to enhance resource acquisition, remains a missing link in this RES. Here, we argue that incorporating root exudation into the structure of RES is key to a holistic understanding of soil nutrient acquisition. We highlight the different functional roles of root exudates in soil phosphorus (P) and nitrogen (N) acquisition. Thereafter, we synthesize emerging evidence that illustrates how root exudation interacts with root morphology and mycorrhizal symbioses at the level of species and individual plant and argue contrasting patterns in species evolved in P‐impoverished vs N‐limited environments. Finally, we propose a new conceptual framework, integrating three groups of root functional traits to better capture the complexity of belowground resource‐acquisition strategies. Such a deeper understanding of the integrated and dynamic interactions of root morphology, root exudation, and mycorrhizal symbioses will provide valuable insights into the mechanisms underlying species coexistence and how to explore belowground interactions for sustainable managed systems.